Process Design and Modelling of the Production of Butyl Cellosolve Acetate and EO-3 Phosphate Ester - Lupete K Bhullar; Zulpan Adi Putra (Universitas Pendidikan Indonesia, 2017)
A chemical company has identified that Butyl Cellosolve Acetate (BCA) and EO-3 Phosphate Ester (EO-3 PE) esters have significant potential in a large variety of applications. However, there is limited information in existing practices involving these particular grades of esters. Hence, the aim of the present work is to develop the process design for the production of these two esters. Within the development stage, the technical and economic challenges of the production processes are evaluated and compared. The results show that, among other things, the BCA process shows the formation of azeotropic mixtures which causes the separation process to be difficult. On the other hand, EO-3 PE shows the formation of aqueous phosphoric acid that is also difficult to separate. Fortunately, this aqueous phosphoric acid can be sold, which then increase the economic attractiveness of the developed process. Monte Carlo simulation were performed to account some uncertainties such as CAPEX estimate, raw material prices and product prices. This simulation shows that the developed BCA process has a significant chance to be non-profitable, while the economic potential of the EO-3 PE process is at least 200% higher than that of the BCA process in all scenarios.